2022
DOI: 10.37256/cm.3420221711
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Method for Approximate Solution of Scattering of Surface Waves by Thin Vertical Barrier Over a Stepped Bottom Topography

Abstract: A study on interaction of surface water waves by thin vertical rigid barrier over a step type bottom topography is analysed. The associated mixed boundary value problem is solved using the eigenfunction expansion of the velocity potential. The resulting system of equations, avoiding the traditional approach of employing application of orthogonality relations, is solved using algebraic least squares method giving rise the numerical values of the reflection and transmission coefficients by the barrier over step.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Specifically, David Hesten and Elie Cartan are notable contributors to the progress and development of Clifford algebra. Elie Cartan presented the idea of the spinor in 1913 and in 1938 the idea of the pure spinor and he defined Clifford algebra's as algebras of matrices and found that 8 has a periodicity inside these algebraic structures, for more info, refer [8]. David Hesten extended the concept of "Clifford Algebra" to devise a formalism and calls it Geometric Algebra [6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, David Hesten and Elie Cartan are notable contributors to the progress and development of Clifford algebra. Elie Cartan presented the idea of the spinor in 1913 and in 1938 the idea of the pure spinor and he defined Clifford algebra's as algebras of matrices and found that 8 has a periodicity inside these algebraic structures, for more info, refer [8]. David Hesten extended the concept of "Clifford Algebra" to devise a formalism and calls it Geometric Algebra [6].…”
Section: Introductionmentioning
confidence: 99%